The contacts of the Philistines and the Israelites in the twelfth and eleventh centuries B.C. : an archaeological and historical study - Van Schalkwyk, Johan,1947- (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Phil.) -- University of Stellenbosch, 1974.